Cultivation of Islamic philanthropy concept through high impact educational practices in Universiti Teknologi MARA / Noor Syahida Md Soh ... [et al.] - Md Soh, Noor Syahida; Ismail, Huzaimah; Md Hassan, Nurulhuda; Ayob, Mohd Annas Shafiq; Mohd Sairi, Faridah (Universiti Teknologi MARA, 2022)
Education in Malaysia is aimed to shape noble and highly skilled individuals. The advancement of the education system have led to Education 5.0, emphasizing the qalbu (soul) teaching concept. In 2019, the General Education Subjects (MPU) implementation structure, which aims to cultivate skills, social responsibilities, values, attitudes, and professionalism, improved with more comprehensive teaching methods. Ministry of Education Malaysia (2019) has also outlined High Impact Educational Practices (HIEPs) Guidelines. Thus, this research will discuss the cultivation of Islamic philanthropy concepts through HIEPs in MPU courses of U1 group (Degree). This research has applied the document analysis method by analyzing and comparing 11 related Islamic Philanthropy articles with HIEPs documents for MPU courses. The data obtained is abductively analyzed via ATLAS.ti8 software. The research finding has discovered three Islamic philanthropy concepts: driving element, benefit element, and execution element. Based on the mentioned elements, Islamic Philanthropy's cultivation in MPU courses can be implemented through HIEPs. The Ministry of Education Malaysia has outlined it as the learning methods based on service or community and invention and innovation exhibition. The cultivation of Islamic Philanthropy through HIEPs can contribute to the students' benefits by inculcating values and developing good morals through their learning experiences.